Potensi Antibakteri Lidah Buaya, Kalsium Hidroksida, dan Omeprazole Terhadap Enterococcus faecalis - Hana Kartika, Adityarini; Suwartini, Tien; Tri Oka Binartha, Ciptadhi (Jurnal Kedokteran Gigi Terpadu, 2025)
This literature review aims to evaluate the efficacy of various intracanal medicaments in root canal therapy, particularly against Enterococcus faecalis, a common pathogen responsible for endodontic treatment failure. Calcium hydroxide remains the most commonly used intracanal medicament due to its high pH and ability to induce hard tissue formation. However, its efficacy against E. faecalis is limited. Proton pump inhibitors such as omeprazole have shown potential in enhancing the antibacterial properties of calcium hydroxide. In addition, herbal alternatives such as Aloe barbadensis miller (Aloe vera) have shown promising antibacterial effects with a lower toxicity profile compared to traditional medicaments. Although calcium hydroxide is effective in certain aspects of endodontic therapy, its limitations against persistent pathogens such as E. faecalis require exploration of additional or alternative intracanal medicaments. Proton pump inhibitors and herbal extracts such as aloe vera offer promising avenues for improving root canal treatment outcomes.